Catalytic cracking catalyst as well as preparation method and application thereof
By using rare earth modified molecular sieve with low sulfate content and high crystallinity, the problem of insufficient catalyst activity stability and heavy oil conversion capacity is solved, and efficient diesel yield and heavy oil are achieved The conversion rate is suitable for catalytic cracking of heavy oil, meeting the seasonal changes in market demand.
Patent Information
- Application Number
- CN202310812381.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-04
- Publication Date
- 2025-01-07
AI Technical Summary
The existing catalytic cracking catalysts lack activity stability during heavy oil conversion, resulting in low diesel yield and insufficient heavy oil conversion capacity, which cannot meet the demand for oversupply of diesel but the market has seasonal shortage.
The rare earth modified molecular sieve is used in combination with phosphorus oxide and magnesium oxide through low sulfate content and high crystallinity and good stability. The crystallinity and stability of the molecular sieve are improved by rare earth ion exchange and precipitant treatment, and combined with P and Mg element controls to form a catalyst with high activity stability and heavy oil conversion ability.
The catalytic cracking catalyst has good activity stability, high conversion rate of heavy oil and high diesel yield. It is suitable for catalytic cracking of heavy oil, improves diesel yield and meets the seasonal changes in market demand.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalyst preparation, and in particular to a catalytic cracking catalyst and a preparation method thereof, and application of the catalytic cracking catalyst in heavy oil catalytic cracking. Background Art
[0002] The catalytic cracking unit is still one of the most important units in my country's refining process. About 70% of gasoline, 40% of diesel and 35% of propylene come from the catalytic cracking unit. The most important use of diesel is in diesel engines for vehicles and ships. Compared with gasoline engines, diesel engines have higher thermal efficiency, greater power, lower fuel consumption and are more economical, so some small cars and even high-performance cars have switched to diesel.
[0003] From 2010 to 2020, my country's diesel production generally showed a trend of first rising and then falling. In 2017, diesel production increased by 16.417 million tons compared with 2011, reaching a peak of 183.18 million tons. However, my country's diesel consumption has certain seasonal characteristics. The diesel peak season occurs in spring and autumn every year, especially from September to November. This is the busy farming season, the coastal fishing moratorium ends one after another, the demand for diesel oil in fisheries increases, the "plum rain" in the south ends, and the rainy days in the north decrease. Infrastructure, industrial and mining production, and logistics and transportation all enter an active production cycle. During this period, including the logistics prosperity index and China's water and land transportation cargo turnover will also be at a relatively high level throughout the year. From another dimension, the diesel-crude oil price difference from September to November each year will generally be higher than other months, which is an important sign of the peak season for diesel consumption. In particular, gasoline has been significantly unsalable in recent years, diesel demand has continued to increase, and the diesel-gasoline consumption ratio has increased significantly. At the same time, for countries with backward infrastructure such as Africa, the power facilities are very backward and all rely on diesel power generation, and the demand for diesel is usually high.
[0004] In summary, although diesel supply exceeds demand overall, diesel still has a special market shortage phenomenon, and diesel shortages will occur in different regions and seasons. Therefore, on the basis of efficient conversion of heavy oil, how to increase the yield of catalytic cracking diesel is still an important research topic for oil refiners.
[0005] The basic design idea of catalytic cracking diesel catalyst is that the catalyst should have suitable acid strength and acid density distribution, strong heavy oil cracking ability, convert heavy oil into diesel, and inhibit further cracking of diesel fraction by strong acid. US4843052, US4940531, US5248642 and others mainly use modified kaolin to improve catalytic cracking diesel yield; CN1217231 discloses a phosphorus-modified zeolite, which can improve diesel yield; CN1307087, CN1069513 disclose a technology of increasing diesel production by compounding Y-type zeolite and selective zeolite as catalyst active components; CN1861754A discloses a method of improving diesel yield by using kaolin microspheres after alkali treatment; CN1683474A discloses a method of improving diesel yield by using kaolin in-situ crystallized microspheres after magnesium modification.
[0006] Existing patented technologies can all improve diesel yields, and the mainstream technology is still to increase diesel yields by regulating the acidity of molecular sieves through elements such as P and Mg. However, due to the insufficient activity stability of the Y-type molecular sieve modified by the active component RE, the heavy oil conversion capacity of the catalyst is insufficient and the oil slurry increases during the process of regulating the acidity of the molecular sieves with elements such as P and Mg. Therefore, technological innovation is needed to improve the activity stability of the Y-type molecular sieve, thereby improving the activity, stability and heavy oil conversion capacity of the catalytic cracking catalyst and the diesel yield. Summary of the invention
[0007] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a catalytic cracking catalyst, which comprises a rare earth modified molecular sieve with low sulfate content, high crystallinity and good stability, so that in the process of regulating the acid strength of the molecular sieve by elements such as P and Mg, the heavy oil conversion capacity can be maintained strong while the diesel yield can be improved. The catalyst is used in the catalytic cracking reaction of heavy oil and has the characteristics of good activity stability, high heavy oil conversion rate and high diesel yield.
[0008] In order to achieve the above object, the first aspect of the present invention provides a catalytic cracking catalyst, wherein the catalytic cracking catalyst contains a catalytic cracking active component, wherein the catalytic cracking active component contains: a rare earth modified molecular sieve, phosphorus oxide and magnesium oxide; SO4 in the rare earth modified molecular sieve 2- Content ≤1wt%.
[0009] The second aspect of the present invention provides a method for preparing the catalytic cracking catalyst according to the first aspect, the preparation method comprising:
[0010] The catalytic cracking active component is mixed and contacted with a macroporous material source and a clay source in a solution state to obtain a catalyst precursor, which is optionally shaped, and then optionally dried and calcined;
[0011] Preferably, the preparation method comprises:
[0012] (1) mixing the rare earth modified molecular sieve, phosphorus source and water to make a slurry, then adding a macroporous material source, a binder source and a clay source to mix and homogenize, dry and calcine to obtain catalyst solid particles;
[0013] (2) The catalyst solid particles obtained in step (1), water, a magnesium source and optionally an ammonium source are mixed, filtered, washed with water and dried to obtain a catalytic cracking catalyst.
[0014] The third aspect of the present invention provides a use of the catalytic cracking catalyst described in the first aspect in catalytic cracking of heavy oil.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] (1) The catalytic cracking catalyst provided by the present invention has the characteristics of good activity stability, high heavy oil conversion rate and high diesel yield by using a rare earth modified molecular sieve with low sulfate, high crystallinity, strong acidity and good stability in combination with phosphorus oxide and magnesium oxide;
[0017] (2) The rare earth modified molecular sieve provided by the present invention is preferably prepared by adding a precipitant (i.e., a first precipitant and a second precipitant) to the Na-type molecular sieve after rare earth ion exchange and before ammonium sulfate exchange to form a precipitate precursor of rare earth oxide with rare earth ions, thereby avoiding the formation of precipitation with sulfate ions by free rare earth ions in the exchange system solution, on the surface of the molecular sieve or in the supercage during the subsequent sodium reduction process of ammonium sulfate exchange, thereby achieving the purpose of reducing sulfate ions, thereby improving the crystallinity and stability of the molecular sieve while improving the utilization rate of rare earths, so that the molecular sieve has the characteristics of low sulfate ions, high crystallinity, strong acidity and good stability. In the subsequent process of regulating the acidity strength of the molecular sieve by elements such as P and Mg, the heavy oil conversion capacity can be maintained while the diesel yield can be improved;
[0018] (3) The preparation method of the catalytic cracking catalyst provided by the present invention has the characteristics of simple operation, simplified process flow, and easy to realize industrial production. P and Mg are used to adjust the catalyst to have appropriate acidity, thereby controlling the ratio of different reactions in the cracking process, and improving the catalyst's heavy oil conversion capacity and diesel yield;
[0019] (4) The catalytic cracking catalyst provided by the present invention is particularly suitable for catalytic cracking of heavy oil. In the process of catalytic cracking of heavy oil, it can not only show high catalytic cracking activity but also obtain a high diesel yield. DETAILED DESCRIPTION
[0020] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0021] The first aspect of the present invention provides a catalytic cracking catalyst, wherein the catalytic cracking catalyst contains a catalytic cracking active component, wherein the catalytic cracking active component contains: a rare earth modified molecular sieve, phosphorus oxide and magnesium oxide; SO4 in the rare earth modified molecular sieve 2- Content ≤1wt%.
[0022] In the present invention, the catalytic cracking catalyst provided by the present invention is characterized by good activity stability, high heavy oil conversion rate and high diesel yield by combining a rare earth modified molecular sieve with low sulfate content, high crystallinity, strong acidity and good stability with phosphorus oxide and magnesium oxide.
[0023] According to a preferred embodiment of the present invention, the SO4 2- The content is ≤0.5wt%, preferably 0.01-0.45wt%. The above-mentioned implementation method can improve the crystallinity and stability of the rare earth modified molecular sieve, and at the same time improve the utilization rate of rare earth, so that in the process of regulating the acid strength of the molecular sieve by elements such as P and Mg, the heavy oil conversion capacity can be maintained while improving the diesel yield, and it has the characteristics of good activity stability, high heavy oil conversion rate and high diesel yield. In the present invention, unless otherwise specified, SO4 2- The content parameters were measured by XRF fluorescence method.
[0024] According to a preferred embodiment of the present invention, the crystallinity of the rare earth modified molecular sieve is 50-80%. By adopting the above-mentioned embodiment, the stability of the rare earth modified molecular sieve can be improved, and the rare earth modified molecular sieve with high crystallinity and good stability is used in combination with phosphorus oxide and magnesium oxide, and has the characteristics of good activity stability, high heavy oil conversion rate and high diesel yield. In the present invention, without special circumstances, the crystallinity parameter is measured by X-ray diffraction.
[0025] According to a preferred embodiment of the present invention, the sodium content in the rare earth modified molecular sieve is not more than 1.2wt%, preferably 0.6-1.0wt%, calculated as Na2O. By adopting the above embodiment, a catalytic cracking catalyst with good activity stability, high heavy oil conversion rate and high diesel yield can be obtained.
[0026] According to a preferred embodiment of the present invention, the rare earth content in the rare earth modified molecular sieve is 5-20wt%, preferably 6-18wt%, calculated as RE2O3. The above embodiment can improve the activity stability of the rare earth modified molecular sieve, and by regulating the acidity strength of the molecular sieve by elements such as P and Mg, a catalytic cracking catalyst with good activity stability, high heavy oil conversion rate and high diesel yield can be obtained.
[0027] According to a preferred embodiment of the present invention, based on the total weight of the catalytic cracking catalyst, the phosphorus oxide is calculated as P2O5, and the magnesium oxide is calculated as MgO, and the catalytic cracking catalyst contains: 15-30% by weight of rare earth modified molecular sieve, 0.5-3% by weight of phosphorus oxide, and 0.2-1.5% by weight of magnesium oxide. By adopting the above embodiment, by adjusting the content of each component within the above range, a catalytic cracking catalyst with good activity stability, high heavy oil conversion rate, and high diesel yield can be obtained.
[0028] In the present invention, the rare earth modified molecular sieve has a wide range of molecular sieve types, and all commonly used molecular sieves can be used in the present invention. According to a preferred embodiment of the present invention, the rare earth modified molecular sieve is a rare earth modified Y-type molecular sieve. By adopting the above embodiment, a catalytic cracking catalyst with good activity stability, high heavy oil conversion rate and high diesel yield can be obtained.
[0029] According to a preferred embodiment of the present invention, the catalytic cracking catalyst contains a macroporous material, clay, the catalytic cracking active component and optionally a binder.
[0030] According to a preferred embodiment of the present invention, the macroporous material is selected from macroporous alumina and / or macroporous silicon-alumina material, preferably macroporous silicon-alumina material. Preferably, the specific surface area of the macroporous silicon-alumina material is 400-500m 2 / g, pore volume is 1-1.5ml / g, and average pore size is 40-50nm. The above-mentioned implementation method is beneficial to the diffusion and precracking of heavy oil macromolecules, and a catalytic cracking catalyst with better activity stability, higher heavy oil conversion rate and higher diesel yield can be obtained. In the present invention, the specific surface area, pore volume and average pore size of the macroporous material are all measured by low-temperature nitrogen adsorption-desorption method, and the instrument used is the physical and chemical adsorption instrument TriStar3020 of Micro meritics Company of the United States, and the test standard is the enterprise standard NB / SH / T 0959.
[0031] According to a preferred embodiment of the present invention, the clay is selected from at least one of kaolin, halloysite, porphyrite, diatomite and vesicle, preferably kaolin. The above embodiment can effectively play a role in thermal protection and active dilution of the rare earth modified molecular sieve.
[0032] According to a preferred embodiment of the present invention, the binder is selected from at least one of silicon dioxide, aluminum oxide, and phosphorus pentoxide, preferably aluminum oxide. In the present invention, the binder is obtained by converting the binder source after calcination. By adopting the above embodiment, a catalytic cracking catalyst with good wear resistance can be prepared, ensuring that it can reduce wear during application.
[0033] According to a preferred embodiment of the present invention, the catalytic cracking catalyst contains rare earth modified molecular sieve, macroporous material, binder, clay, phosphorus oxide and magnesium oxide. Based on the total weight of the catalytic cracking catalyst, phosphorus oxide is calculated as P2O5, and magnesium oxide is calculated as MgO. The catalytic cracking catalyst contains: 15-30% by weight of rare earth modified molecular sieve, 2-15% by weight of macroporous material, 5-30% by weight of binder, 40-75% by weight of clay, 0.5-3% by weight of phosphorus oxide, and 0.2-1.5% by weight of magnesium oxide. By adopting the above embodiment, a catalytic cracking catalyst with good activity stability, high heavy oil conversion rate and high diesel yield can be obtained by regulating the content of each component within the above range.
[0034] The rare earth modified molecular sieves having the above-mentioned characteristics of the present invention can achieve the purpose of the present invention, and there is no special requirement for their preparation methods. According to the present invention, a preparation method of a rare earth modified molecular sieve is provided.
[0035] According to a preferred embodiment of the present invention, the method for preparing the rare earth modified molecular sieve comprises the following steps:
[0036] (1) exchanging rare earth ions on a Na-type molecular sieve to obtain a rare earth ion exchange slurry;
[0037] (2) adding a first precipitant to cause a portion of the rare earth ions in the rare earth ion exchange slurry to undergo a first precipitation to obtain a first precipitation slurry;
[0038] (3) the first precipitation slurry is filtered, subjected to a first ammonium sulfate exchange, subjected to a first water wash, and subjected to a first roasting in sequence to obtain a cross-exchanged and roasted molecular sieve dry powder;
[0039] (4) adding a second precipitant to cause a second precipitation of some rare earth ions in the cross-calcined molecular sieve dry powder, and then sequentially performing a second ammonium sulfate exchange, a second water washing, and optionally a second calcination to obtain a rare earth modified molecular sieve.
[0040] In the present invention, the rare earth modified molecular sieve is the main active component of the catalytic cracking catalyst, and its performance determines the performance of the catalytic cracking catalyst. The rare earth modified molecular sieve provided by the present invention is prepared by adding a precipitant (i.e., a first precipitant and a second precipitant) to the Na type molecular sieve after rare earth ion exchange and before ammonium sulfate exchange, and generating a precipitate precursor of rare earth oxide with rare earth ions, thereby avoiding the formation of precipitation with sulfate radicals in the exchange system solution, on the surface of the molecular sieve or in the super cage in the subsequent sodium reduction process of ammonium sulfate exchange, so as to achieve the purpose of reducing the sulfate radical content in the molecular sieve, thereby improving the crystallinity and stability of the molecular sieve while improving the utilization rate of rare earths, so that the molecular sieve has the characteristics of low sulfate radicals, high crystallinity, strong acidity and good stability, and is used as an active component of the catalytic cracking catalyst, and the cracking activity and hydrothermal stability of the catalytic cracking catalyst are also correspondingly improved, and in the subsequent process of regulating the acid strength of the molecular sieve by elements such as P and Mg, the heavy oil conversion capacity can be maintained strong while improving the diesel yield.
[0041] In the present invention, unless otherwise specified, "first" and "second" do not indicate a sequence, nor do they limit the materials or steps, but are only used to distinguish that they are not the same steps or materials. For example, "first" and "second" in "first ammonium sulfate exchange" and "second ammonium sulfate exchange" are only used to indicate that they are not the same ammonium sulfate exchange.
[0042] According to a preferred embodiment of the present invention, in step (1), the rare earth ion exchange process comprises: mixing the Na-type molecular sieve with water and then adding a soluble rare earth source to perform the rare earth ion exchange.
[0043] According to a preferred embodiment of the present invention, in step (1), the weight ratio of the Na-type molecular sieve to water is 1:(1.5-30), for example, 1:1.5, 1:2, 1:3, 1:4, 1:5, 1:10, 1:20, 1:30, and any value in the range of any two numerical values, preferably 1:(2-5).
[0044] According to a preferred embodiment of the present invention, in step (1), the mass ratio of the soluble rare earth source in terms of RE2O3 to the amount of the Na-type molecular sieve in terms of dry basis is 1-20:100, for example, 1:100, 4:100, 6:100, 10:100, 14:100, 16:100, 20:100, and any value in the range of any two values, preferably 6-16:100. The aforementioned embodiment is more conducive to reducing the sulfate content in the rare earth modified molecular sieve, thereby eliminating the effect of sulfate on the performance of the rare earth modified molecular sieve, and thus improving the crystallinity, stability and catalytic performance of the rare earth modified molecular sieve.
[0045] According to a preferred embodiment of the present invention, in step (1), the conditions for rare earth ion exchange include: temperature of 25-180°C, preferably 50-80°C; and / or pH of 2.8-6.5, preferably 3.5-4.5; and / or time of 0.3-3.5h, preferably 0.5-1.5h. The above embodiment can better exchange rare earth ions with Na-type molecular sieves, which is more conducive to reducing the sulfate content in the rare earth modified molecular sieve, thereby eliminating the effect of sulfate on the performance of the rare earth modified molecular sieve, thereby improving the crystallinity, stability and catalytic performance of the rare earth modified molecular sieve.
[0046] The present invention does not specifically limit the type of the Na-type molecular sieve, and the Na-type molecular sieve is well known to those skilled in the art. According to a preferred embodiment of the present invention, in step (1), the silicon-aluminum ratio of the Na-type molecular sieve is 2-100:1, preferably 2-50:1; more preferably, the Na-type molecular sieve is selected from at least one of NaY molecular sieve, NaHY molecular sieve, NaUSY molecular sieve, NaREHY molecular sieve and NaREUSY molecular sieve, preferably NaY molecular sieve and / or NaHY molecular sieve.
[0047] In the present invention, during the rare earth ion exchange process, the rare earth ions in the soluble rare earth source are completely attached to the surface and internal pores of the Na-type molecular sieve. Therefore, the weight ratio of the Na-type molecular sieve and the soluble rare earth source in terms of RE2O3 on a dry basis is 100:(1-20), preferably 100:(6-16). In the present invention, unless otherwise specified, solubility refers to being easily soluble in water or being easily soluble in water under the action of an auxiliary agent. According to a preferred embodiment of the present invention, in step (1), the soluble rare earth source is selected from chlorates and / or nitrates containing rare earth elements, wherein the rare earth is selected from at least one of lanthanum, cerium and yttrium, preferably lanthanum and / or yttrium.
[0048] According to a preferred embodiment of the present invention, in step (2), the amount of the first precipitant is such that the molar ratio of the rare earth ions in the Na-type molecular sieve is 1-4wt% after the first precipitation; further preferably, the amount of the first precipitant is such that the molar ratio of the rare earth ions in the Na-type molecular sieve is 1.5-2.5wt% after the first precipitation. The above embodiment is more conducive to reducing the content of sulfate in the rare earth modified molecular sieve, thereby eliminating the influence of sulfate on the performance of the rare earth modified molecular sieve, and then improving the crystallinity, stability and catalytic performance of the rare earth modified molecular sieve.
[0049] According to a preferred embodiment of the present invention, in step (2), the conditions of the first precipitation include: a temperature of 25-180°C, preferably 50-80°C; and / or a time of 0.1-5h, preferably 0.1-2h. The above-mentioned embodiment can better promote the first precipitant and rare earth ions to form a precipitated precursor of rare earth oxides, avoid the formation of precipitation of free rare earth ions and sulfate in the exchange system solution, on the surface of the molecular sieve or in the super cage during the subsequent ammonium sulfate exchange and sodium reduction process, and achieve the purpose of reducing the sulfate content in the molecular sieve, thereby improving the crystallinity and stability of the molecular sieve and the utilization rate of rare earth.
[0050] The present invention has no special limitation on the type of the first precipitant, as long as it can generate rare earth oxides with the rare earth ions. According to a preferred embodiment of the present invention, in step (2), the first precipitant is selected from at least one of ammonium carbonate, ammonium bicarbonate, ammonium oxalate, ammonium acetate, ammonia water and urea, preferably selected from at least one of ammonium carbonate, ammonium bicarbonate, ammonium oxalate and ammonia water. By adopting the above embodiment, it is possible to preferentially generate a precipitate precursor of rare earth oxides with rare earth ions, avoiding the formation of precipitation of free rare earth ions and sulfate in the exchange system solution, on the surface of the molecular sieve or in the super cage during the subsequent ammonium sulfate exchange and sodium reduction process, thereby achieving the purpose of reducing the sulfate content in the molecular sieve, thereby improving the crystallinity and stability of the molecular sieve and the utilization rate of rare earth.
[0051] In the present invention, the purpose of the first ammonium sulfate exchange is to further exchange the Na + According to a preferred embodiment of the present invention, in step (3), the process of the first ammonium sulfate exchange comprises: exchanging the filtered product with the first ammonium sulfate aqueous solution.
[0052] According to a preferred embodiment of the present invention, in step (3), the weight ratio of the first aqueous ammonium sulfate solution to the Na-type molecular sieve in terms of ammonium sulfate is 5-50:100, for example, 5:100, 10:100, 15:100, 20:100, 25:100, 30:100, 40:100, 50:100, and any value in the range of any two values, preferably 10-25:100. The above embodiment can better exchange the Na in the Na-type molecular sieve. + .
[0053] According to a preferred embodiment of the present invention, in step (3), the concentration of ammonium sulfate in the first aqueous ammonium sulfate solution is 20-400 g / L, for example, 20 g / L, 50 g / L, 80 g / L, 120 g / L, 160 g / L, 200 g / L, 250 g / L, 300 g / L, 400 g / L, and any value in the range of any two values, preferably 120-250 g / L. The above embodiment can better exchange the Na in the Na type molecular sieve. + .
[0054] According to a preferred embodiment of the present invention, in step (3), the conditions for the first ammonium sulfate exchange include: a temperature of 15-150°C, preferably 50-80°C; and / or a time of 0.1-5h, preferably 0.5-2h. The above embodiment can better perform the first ammonium sulfate exchange, and further exchange the Na in the Na molecular sieve. + .
[0055] According to a preferred embodiment of the present invention, in step (3), the amount of water used in the first water wash is 1-8 times the weight of the Na-type molecular sieve, for example, 1 times, 2 times, 3 times, 5 times, 7 times, 8 times, and any value in the range of any two values, preferably 2-5 times.
[0056] According to a preferred embodiment of the present invention, in step (3), the conditions of the first calcination include: 100% water vapor atmosphere; and / or a temperature of 400-700°C, preferably 500-650°C; and / or a time of 0.1-5h, preferably 0.5-3h.
[0057] According to a preferred embodiment of the present invention, in step (4), the amount of the second precipitant is such that the content of 0.5-3wt% of rare earth ions in the cross-roasted molecular sieve powder is precipitated by the second precipitate; further preferably, the amount of the second precipitant is such that the content of 1-2wt% of rare earth ions in the cross-roasted molecular sieve powder is precipitated by the second precipitate. By adopting the above embodiment, the content of sulfate in the rare earth modified molecular sieve can be further reduced, thereby better eliminating the influence of sulfate on the performance of the rare earth modified molecular sieve, and further improving the crystallinity, stability and catalytic performance of the rare earth modified molecular sieve.
[0058] According to a preferred embodiment of the present invention, in step (4), the conditions of the second precipitation include: a temperature of 15-40°C, preferably 20-30°C; and / or a time of 0.1-5h, preferably 0.1-2h. The above embodiment can better promote the second precipitant and rare earth ions to form a precipitated precursor of rare earth oxides, avoid the formation of precipitation of free rare earth ions and sulfate in the exchange system solution, on the surface of the molecular sieve or in the super cage during the subsequent ammonium sulfate exchange and sodium reduction process, and achieve the purpose of reducing the sulfate content in the molecular sieve, thereby improving the crystallinity and stability of the molecular sieve and the utilization rate of rare earth.
[0059] According to a preferred embodiment of the present invention, in step (4), the second precipitant is selected from at least one of ammonium carbonate, ammonium bicarbonate, ammonium oxalate, ammonium acetate, ammonia and urea, and is preferably selected from at least one of ammonium carbonate, ammonium bicarbonate, ammonium oxalate and ammonia. By adopting the above embodiment, it is possible to preferentially react with rare earth ions to form a precipitate precursor of rare earth oxides, thereby avoiding the formation of precipitation by free rare earth ions and sulfate in the exchange system solution, on the surface of the molecular sieve or in the super cage during the subsequent ammonium sulfate exchange and sodium reduction process, thereby achieving the purpose of reducing the sulfate content in the molecular sieve, thereby improving the crystallinity and stability of the molecular sieve and the utilization rate of rare earth.
[0060] According to a preferred embodiment of the present invention, in step (4), the second ammonium sulfate exchange process comprises: exchanging the second precipitated product with the second ammonium sulfate aqueous solution.
[0061] According to a preferred embodiment of the present invention, in step (4), the weight ratio of the second aqueous ammonium sulfate solution to the cross-baked molecular sieve powder in terms of ammonium sulfate is 5-50:100, for example, 5:100, 10:100, 15:100, 20:100, 25:100, 30:100, 40:100, 50:100, and any value in the range consisting of any two values, preferably 10-25:100.
[0062] According to a preferred embodiment of the present invention, in step (4), the concentration of ammonium sulfate in the second aqueous ammonium sulfate solution is 20-400 g / L, for example, 20 g / L, 50 g / L, 80 g / L, 120 g / L, 150 g / L, 200 g / L, 250 g / L, 300 g / L, 400 g / L, and any value in the range consisting of any two values, preferably 120-250 g / L.
[0063] According to a preferred embodiment of the present invention, in step (4), the conditions for the second ammonium sulfate exchange include: a temperature of 20-85°C, preferably 50-80°C; and / or a time of 0.1-5h, preferably 0.1-2h. The above embodiment can better perform the second ammonium sulfate exchange and further exchange the Na in the Na molecular sieve. + .
[0064] According to a preferred embodiment of the present invention, in step (4), the amount of water used in the second water washing is 1-8 times the weight of the cross-baked molecular sieve dry powder, for example, 1 time, 2 times, 3 times, 4 times, 5 times, 8 times, and any value in the range of any two values, preferably 2-5 times.
[0065] According to a preferred embodiment of the present invention, in step (4), the conditions of the second calcination include: 20-100% water vapor atmosphere; and / or temperature of 400-700°C, preferably 450-650°C; and / or time of 0.1-10h, preferably 0.5-5h.
[0066] According to a preferred embodiment of the present invention, in step (4), before the second precipitation, the cross-baked molecular sieve dry powder and water are mixed.
[0067] According to a preferred embodiment of the present invention, in step (4), the weight ratio of the cross-baked molecular sieve dry powder to water is 1:(1.5-30), for example, 1:1.5, 1:2, 1:3, 1:4, 1:5, 1:10, 1:20, 1:30, and any value in the range consisting of any two values, preferably 1:(2-5).
[0068] The catalytic cracking catalysts having the above-mentioned characteristics of the present invention can achieve the purpose of the present invention, and there is no special requirement for their preparation methods.
[0069] The second aspect of the present invention provides a method for preparing the catalytic cracking catalyst described in the first aspect, the preparation method comprising: mixing and contacting the catalytic cracking active component with a macroporous material source and a clay source in a solution state to obtain a catalyst precursor, optionally performing molding, and then optionally drying and calcining.
[0070] According to a preferred embodiment of the present invention, the preparation method comprises:
[0071] (1) mixing the rare earth modified molecular sieve, phosphorus source and water to make a slurry, then adding a macroporous material source, a binder source and a clay source to mix and homogenize, dry and calcine to obtain catalyst solid particles;
[0072] (2) The catalyst solid particles obtained in step (1), water, a magnesium source and optionally an ammonium source are mixed, filtered, washed with water and dried to obtain a catalytic cracking catalyst.
[0073] In the present invention, the preparation method of the catalytic cracking catalyst provided by the present invention has the characteristics of simple operation, simplified process flow, and easy to realize industrial production. P and Mg are used to regulate its suitable acidity, thereby controlling the proportion of different reactions in the cracking process, and improving the catalyst's heavy oil conversion capacity and diesel yield.
[0074] According to a preferred embodiment of the present invention, in step (1), based on 100 parts of the dry basis weight of the catalyst, the phosphorus source is calculated as P2O5, 15-30 parts of rare earth modified molecular sieve, 0.5-3 parts of phosphorus source, 2-15 parts of macroporous material source, 5-30 parts of binder source, 40-75 parts of clay source and water are mixed to form a slurry with a solid content of 25-50wt%. By adopting the above embodiment, controlling the content of the above components within the preferred range can obtain a catalytic cracking catalyst with good catalytic activity, high heavy oil conversion rate and high diesel yield.
[0075] According to a particularly preferred embodiment of the present invention, in step (1), based on 100 parts of the dry basis weight of the catalyst, the phosphorus source is calculated as P2O5, 18-27 parts of rare earth modified molecular sieve, 0.9-2 parts of phosphorus source, 3-7 parts of macroporous material source, 5.5-25 parts of binder source, 45-65 parts of clay source and water are mixed to form a slurry with a solid content of 35-45wt%. By adopting the above embodiment, the content of each of the above components is controlled within a more preferred range, and a catalytic cracking catalyst with better catalytic activity, higher heavy oil conversion rate and higher diesel yield can be obtained.
[0076] In the present invention, the steps and methods of step (1) of mixing, slurrying, drying and calcining the rare earth modified molecular sieve, phosphorus source, water, macroporous material source, binder source and clay source have no special requirements and can be carried out using conventional techniques, which will not be described in detail in the present invention.
[0077] The present invention has no special requirements on the various raw materials used, and the purpose of the present invention can be achieved as long as the preparation is carried out according to the above steps of the present invention.
[0078] The present invention has no particular limitation on the type of the phosphorus source, and the phosphorus source is a conventional choice in the art. According to a preferred embodiment of the present invention, in step (1), the phosphorus source is selected from at least one of diammonium hydrogen phosphate, ammonium dihydrogen phosphate and ammonium phosphate, preferably diammonium hydrogen phosphate.
[0079] According to a preferred embodiment of the present invention, in step (1), the macroporous material source is selected from macroporous alumina and / or macroporous silica-alumina material, preferably macroporous silica-alumina material.
[0080] The present invention has no particular limitation on the type of the binder source, and the binder source can be any of the existing binders that can be used in catalytic cracking catalysts. According to a preferred embodiment of the present invention, in step (1), the binder source is selected from at least one of aluminum sol, acidified pseudo-boehmite, acidic silica sol and phosphate aluminum sol, preferably aluminum sol and / or acidified pseudo-boehmite, more preferably aluminum sol and acidified pseudo-boehmite.
[0081] According to a preferred embodiment of the present invention, the clay source is selected from at least one of kaolin, halloysite, porphyrolith, diatomaceous earth and vesicle, preferably kaolin.
[0082] The present invention has no special requirements for the steps and methods of drying and calcining, and conventional techniques known to those skilled in the art can be used, which will not be described in detail herein. Specifically, for the present invention, for example, the drying temperature is 100-150°C, and the drying time is 8-15h; the calcining temperature is 400-500°C, and the calcining time is 20-50min.
[0083] According to a preferred embodiment of the present invention, in step (2), the weight ratio of water to catalyst solid particles is 0.5-35:1, based on the dry basis of catalyst solid particles.
[0084] According to a preferred embodiment of the present invention, in step (2), the magnesium source is calculated as MgO based on the dry basis of the catalyst solid particles, and the amount of the magnesium source added is 0.2-1.5wt%, for example, 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt%, 1.0wt%, 1.2wt%, 1.5wt%, and any value in the range of any two values, preferably 0.6-1.2wt%. By adopting the above embodiment, the catalyst is modified by magnesium element and regulated to have suitable acidity, thereby controlling the ratio of different reactions in the cracking process and improving the heavy oil conversion capacity and diesel yield of the catalytic cracking catalyst.
[0085] The present invention does not specifically limit the type of the magnesium source, and the magnesium source is a conventional choice in the art. According to a preferred embodiment of the present invention, in step (2), the magnesium source is selected from magnesium chloride and / or magnesium nitrate, preferably magnesium chloride. By adopting the aforementioned embodiment, the catalyst can be better modified and regulated to have suitable acidity, thereby controlling the ratio of different reactions in the cracking process and improving the heavy oil conversion capacity and diesel yield of the catalytic cracking catalyst.
[0086] The present invention has no particular limitation on the type of the ammonium source, and the ammonium source is a conventional choice in the art. According to a preferred embodiment of the present invention, in step (2), the ammonium source is selected from ammonium chloride and / or ammonium nitrate, preferably ammonium chloride.
[0087] According to a preferred embodiment of the present invention, in step (2), the water washing conditions include: temperature of 20-100°C, preferably 25-50°C; and / or time of 0.1-0.3h, preferably 0.15-0.25h.
[0088] The third aspect of the present invention provides a use of the catalytic cracking catalyst described in the first aspect in catalytic cracking of heavy oil.
[0089] In the present invention, the catalytic cracking catalyst provided by the present invention is particularly suitable for heavy oil catalytic cracking, and can not only show higher catalytic cracking activity during the heavy oil catalytic cracking process, but also obtain a higher diesel yield.
[0090] In the present invention, the catalyst composition is the composition calculated based on the input materials.
[0091] The present invention will be described in detail below through examples.
[0092] The raw materials used in the following examples and comparative examples are as follows:
[0093] NaY molecular sieve: silicon-aluminum ratio 5.1, crystallinity 95%, produced by Changting Catalyst Co., Ltd.;
[0094] Soluble rare earth sources: lanthanum chloride, lanthanum nitrate, yttrium chloride, all industrial products, collected from the catalyst plant of Lanzhou Petrochemical Company;
[0095] Ammonium sulfate, ammonium oxalate, ammonium carbonate, ammonia water, ammonium chloride, diammonium phosphate, and magnesium chloride were all of analytical grade;
[0096] Pseudo-boehmite (ignition loss 36.7%), kaolin (ignition loss 18.4%), macroporous silicon-alumina material (solid content 15.4%, pore volume 1.15 ml / g, specific surface area 458 m 2 / g, average pore size 43.5nm) solid; aluminum sol, containing 22.6% by weight of aluminum oxide; silica sol, containing 30.5% by weight of silicon oxide, all of which are industrial qualified products.
[0097] In the following examples and comparative examples:
[0098] Determination of SO4 in rare earth modified Y-type molecular sieve by XRF fluorescence method 2- content, Na2O content, RE2O3 content, and Na2O content, P2O5 content and MgO content in catalytic cracking catalyst;
[0099] The crystallinity (C / C0) and silicon-aluminum ratio of rare earth modified Y-type molecular sieve were determined by X-ray diffraction.
[0100] Micro-reaction activity test method: the sample was pre-treated at 800℃ and 100% steam for different time periods, the reaction raw material was Dagang light diesel, the reaction temperature was 460℃, the reaction time was 70s, the catalyst loading was 5g, the catalyst-oil weight ratio was 3.2, and the total conversion rate was taken as the micro-reaction activity;
[0101] Evaluation of catalytic cracking reaction selectivity: The selectivity of catalytic cracking reaction was evaluated in the ACE heavy oil microreactor. The catalyst was pre-treated at 800°C and 100% water vapor for 10 hours. The raw oil for the reaction was the raw oil of the 3 million heavy oil catalytic unit of Lanzhou Petrochemical, with the specific composition: 63.2% saturated hydrocarbons, 33.2% aromatic hydrocarbons, and 3.6% colloids; properties include: molecular weight 437g / mol, residual carbon 4.2%; heavy metals include Ca2.2ppm, V4.69ppm, Ni4.42ppm, Fe4.28ppm; reaction temperature is 510°C, and the catalyst-oil ratio is 5.
[0102] Example 1
[0103] (1) Preparation of rare earth modified molecular sieves
[0104] (a) 1000 g (dry basis weight) of NaY molecular sieve was slurried with 5 L of deionized water, and 0.537 L (calculated as La2O3) of 298 g / L LaCl3 solution (La 3+ 0.98 mol) was subjected to rare earth ion exchange (temperature was 80° C., time was 0.5 h) to obtain a rare earth ion exchange slurry; wherein the content of LaCl3 calculated as La2O3 in the NaY molecular sieve calculated on a dry basis was 16 wt%;
[0105] (b) adding (32 g, 0.225 mol) ammonium oxalate monohydrate to make 2.4 wt% of La in the rare earth ion exchange slurry 3+ Performing a first precipitation (temperature of 80° C., time of 0.5 h) to obtain a first precipitation slurry;
[0106] (c) filtering the first precipitate slurry, draining it, adding 0.833 L of 180 g / L ammonium sulfate aqueous solution, exchanging at 60° C. for 1 h, draining it, rinsing it with 3 L of water, and then calcining it at 500° C. for 2 h in a 100% water vapor atmosphere to obtain a cross-calcined molecular sieve dry powder;
[0107] (d) 1000 g (dry basis) of the cross-roasted molecular sieve powder was slurried with 5 L of deionized water, and then 25.6 g, 0.18 mol, of ammonium oxalate monohydrate was added to make 2 wt % of La in the cross-roasted molecular sieve powder. 3+After the second precipitation (temperature 25°C, time 0.5h), 0.6L of 250g / L ammonium sulfate aqueous solution was added, exchanged at 80°C for 1.5h, filtered, drained, rinsed with 5L of water, and calcined at 450°C in a 100% water vapor atmosphere for 2h to obtain rare earth modified Y-type molecular sieve Z1;
[0108] (2) Preparation of catalytic cracking catalyst
[0109] Based on 100 parts of the dry mass of the catalyst, 23 parts by weight of the rare earth modified Y-type molecular sieve Z1 and 1.1 parts by weight of ammonium dihydrogen phosphate (calculated as P2O5) were mixed with water and slurried for 30 minutes, and then 57.9 parts by weight of kaolin, 6 parts by weight of macroporous silica-alumina material, 6 parts by weight of aluminum sol, and 6 parts by weight of acidified pseudo-boehmite were added, and mixed at 25°C for 1 hour to obtain a slurry with a solid content of 48wt%, and then homogenized and spray-formed in sequence, and the obtained microspheres were calcined at 450°C for 25 minutes to obtain a catalytic cracking catalyst precursor;
[0110] Based on the dry basis of catalyst solid particles, 200 g of the catalytic cracking catalyst precursor was mixed with water to form a slurry containing the catalyst precursor with a solid content of 20 wt%, and magnesium chloride was added and mixed, wherein the weight ratio of magnesium chloride (calculated as MgO) to the slurry containing the catalyst precursor was 1:100, and then filtered, 1 kg of water (the amount of water used for washing was 5 times the mass of the catalyst precursor) was added, washed at 25° C. for 0.2 h, and dried at 100° C. for 12 h to obtain a catalytic cracking catalyst C1;
[0111] Wherein, based on the total weight of the catalytic cracking catalyst, the Na2O in the catalytic cracking catalyst C1 is + The content is 0.14wt%, the phosphorus content calculated as P2O5 is 1.12wt%, and the magnesium content calculated as MgO is 0.92wt%.
[0112] Example 2
[0113] (1) Preparation of rare earth modified molecular sieves
[0114] (a) 1000 g (dry basis weight) of NaY molecular sieve was slurried with 5 L of deionized water, and 0.358 L of La(NO3)3 solution (La2O3) with a concentration of 280 g / L was added. 3+ 0.615 mol) was subjected to rare earth ion exchange (temperature was 50° C., time was 1.5 h) to obtain a rare earth ion exchange slurry; wherein the content of La(NO3)3 calculated as La2O3 in the NaY molecular sieve calculated on a dry basis was 10 wt%;
[0115] (b) Adding (25.6 g, 0.18 mol) of ammonium oxalate monohydrate can make the 2 wt% La in the above metal ion exchange slurry 3+ Performing a first precipitation (temperature of 50° C., time of 0.5 h) to obtain a first precipitation slurry;
[0116] (c) filtering the first precipitate slurry, draining it, adding 1.111 L of 180 g / L ammonium sulfate aqueous solution, exchanging it at 80° C. for 1 h, draining it, adding 3 L of water for rinsing, and then calcining it at 600° C. for 2 h in a 100% water vapor atmosphere to obtain a cross-calcined molecular sieve dry powder;
[0117] (d) After slurrying the above 1000 g (dry basis) cross-roasted molecular sieve powder with 5 L of deionized water, 13 g (0.135 mol) of ammonium carbonate was added to make the La content in the cross-roasted molecular sieve powder 1.5 wt %. 3+ After the second precipitation (temperature is 25°C, time is 0.5h), 1.666L of 120g / L ammonium sulfate aqueous solution was added, exchanged at 50°C for 1h, filtered, drained, rinsed with 2L of water, and calcined at 500°C for 2.5h in an 80% water vapor atmosphere to obtain a rare earth modified Y-type molecular sieve Z2;
[0118] (2) Preparation of catalytic cracking catalyst
[0119] Based on 100 parts of the dry mass of the catalyst, 27 parts by weight of the rare earth modified Y-type molecular sieve Z2, 1.8 parts by weight of ammonium dihydrogen phosphate (calculated as P2O5) and water were mixed and slurried for 30 minutes, and then 48.7 parts by weight of kaolin, 3 parts by weight of macroporous silicon-aluminum material, 4.5 parts by weight of aluminum sol, and 15 parts by weight of acidified pseudo-boehmite were added, and mixed at 25°C for 1 hour to obtain a slurry with a solid content of 39wt%, and then homogenized and spray-formed in sequence, and the obtained microspheres were calcined at 460°C for 30 minutes to obtain a catalytic cracking catalyst precursor;
[0120] Based on the dry basis of catalyst solid particles, 200 g of the catalytic cracking catalyst precursor was mixed with water to form a slurry containing the catalyst precursor with a solid content of 25 wt%, and magnesium chloride was added and mixed, wherein the weight ratio of magnesium chloride (calculated as MgO) to the slurry containing the catalyst precursor was 0.65:100, and then filtered, 1.6 kg of water (the amount of water used for washing was 8 times the mass of the catalyst precursor) was added, washed at 30° C. for 0.15 h, and dried at 120° C. for 8 h to obtain a catalytic cracking catalyst C2;
[0121] Wherein, based on the total weight of the catalytic cracking catalyst, the Na2O in the catalytic cracking catalyst C2 is +The content is 0.17wt%, the phosphorus content calculated as P2O5 is 1.72wt%, and the magnesium content calculated as MgO is 0.63wt%.
[0122] Example 3
[0123] (1) Preparation of rare earth modified molecular sieves
[0124] (a) 1000 g (dry basis weight) of NaY molecular sieve was slurried with 5 L of deionized water, and 0.407 L of YCl3 solution (Y2O3) with a concentration of 246 g / L was added. 3+ 0.513 mol) was subjected to rare earth ion exchange (temperature was 60° C., time was 1 h) to obtain a rare earth ion exchange slurry; wherein the content of YCl3 calculated as Y2O3 in the NaY molecular sieve calculated on a dry basis was 5.97 wt%;
[0125] (b) adding (32 g, 0.225 mol) ammonium oxalate monohydrate can make 1.7 wt% of Y in the above metal ion exchange slurry 3+ Performing a first precipitation (temperature of 60° C., time of 0.5 h) to obtain a first precipitation slurry;
[0126] (c) filtering the first precipitate slurry, draining it, adding 1.389 L of 180 g / L ammonium sulfate aqueous solution, exchanging at 60° C. for 1.5 h, draining it, rinsing it with 3 L of water, and then calcining it at 650° C. for 2 h in a 100% water vapor atmosphere to obtain a cross-calcined molecular sieve dry powder;
[0127] (d) After slurrying the above 1000 g (dry basis) cross-linked and roasted molecular sieve powder with 5 L of deionized water, 22.6 g (0.16 mol) of ammonium oxalate monohydrate was added to make 1.2 wt% of Y in the above cross-linked and roasted molecular sieve powder. 3+ After the second precipitation (temperature 25°C, time 0.5h), 1.389L of 180g / L ammonium sulfate aqueous solution was added, exchanged at 50°C for 1h, filtered, drained, rinsed with 3L of water, and calcined at 650°C in a 60% water vapor atmosphere for 2h to obtain rare earth modified Y-type molecular sieve Z3;
[0128] (2) Preparation of catalytic cracking catalyst
[0129] Based on 100 parts of the dry mass of the catalyst, 18 parts by weight of the rare earth modified Y-type molecular sieve Z3, 0.9 parts by weight of ammonium dihydrogen phosphate (calculated as P2O5) and water were mixed and slurried for 30 minutes, and then 53.1 parts by weight of kaolin, 7 parts by weight of macroporous silicon-aluminum material, 3 parts by weight of aluminum sol, and 18 parts by weight of acidified pseudo-boehmite were added, and mixed at 25°C for 1 hour to obtain a slurry with a solid content of 36wt%, and then homogenized and spray-formed in sequence, and the obtained microspheres were calcined at 470 for 35 minutes to obtain a catalytic cracking catalyst precursor;
[0130] Based on the dry basis of catalyst solid particles, 200 g of the catalytic cracking catalyst precursor was mixed with water to form a slurry containing the catalyst precursor with a solid content of 20 wt%, and magnesium chloride was added and mixed, wherein the weight ratio of magnesium chloride (calculated as MgO) to the slurry containing the catalyst precursor was 1.2:100, and then filtered, 1 kg of water (the amount of water used for washing was 5 times the mass of the catalyst precursor) was added, washed at 35° C. for 0.25 h, and dried at 110° C. for 10 h to obtain a catalytic cracking catalyst C3;
[0131] Wherein, based on the total weight of the catalytic cracking catalyst, the Na2O in the catalytic cracking catalyst C3 is + The content is 0.10wt%, the phosphorus content calculated as P2O5 is 0.89wt%, and the magnesium content calculated as MgO is 1.13wt%.
[0132] Example 4
[0133] (1) Preparation of rare earth modified molecular sieves
[0134] (a) 1000 g (dry basis) of NaY molecular sieve was slurried with 5 L of deionized water, and 0.43 L (in terms of RE2O3) of a mixed RECl3 solution with a concentration of 326 g / L (the weight ratio of Ce2O3 to La2O3 was 6:4, RE 3+ 0.9287 mol) was subjected to rare earth ion exchange (temperature was 60° C., time was 1 h) to obtain a rare earth ion exchange slurry; wherein the content of RECl3 calculated as RE2O3 in the NaY molecular sieve calculated on a dry basis was 14 wt%;
[0135] (b) Add (25.6 g, 0.18 mol) of ammonium oxalate monohydrate and then add 5 mL of 28% industrial ammonia water to make 2.4 wt% of RE in the rare earth ion exchange slurry. 3+ Performing a first precipitation (temperature of 60° C., time of 0.5 h) to obtain a first precipitation slurry;
[0136] (c) filtering the first precipitated slurry, draining it, adding 1.222 L of 180 g / L ammonium sulfate aqueous solution, exchanging it at 100° C. for 0.5 h, draining it, rinsing it with 5 L of water, and then calcining it at 600° C. for 2 h in a 100% water vapor atmosphere to obtain a cross-calcined molecular sieve dry powder;
[0137] (d) 1000 g (dry basis) of the cross-roasted molecular sieve powder was slurried with 5 L of deionized water, and then 18 g, 0.187 mol, of ammonium carbonate was added to make 1.8 wt% of the RE in the cross-roasted molecular sieve powder. 3+ After the second precipitation (temperature 25°C, time 0.5h), add 1L of 120g / L ammonium sulfate aqueous solution, exchange at 25°C for 1h, filter, drain, add 4L of water for leaching, and calcine at 550°C for 2h in a 20% water vapor atmosphere to obtain rare earth modified Y-type molecular sieve Z4;
[0138] (2) Preparation of catalytic cracking catalyst
[0139] Based on 100 parts of the dry basis mass of the catalyst, 25 parts by weight of the rare earth modified Y-type molecular sieve Z4, 1.5 parts by weight of ammonium dihydrogen phosphate (calculated as P2O5) and water were mixed and slurried for 30 minutes, and then 50.5 parts by weight of kaolin, 5 parts by weight of macroporous silicon-aluminum material, 6 parts by weight of aluminum sol, and 12 parts by weight of acidified pseudo-boehmite were added, and mixed at 25°C for 1 hour to obtain a slurry with a solid content of 42wt%, and then homogenized and spray-formed in sequence, and the obtained microspheres were calcined at 450°C for 40 minutes to obtain a catalytic cracking catalyst precursor;
[0140] Based on the dry basis of catalyst solid particles, 200 g of the catalytic cracking catalyst precursor was mixed with water to form a slurry containing the catalyst precursor with a solid content of 20 wt%, and magnesium chloride was added and mixed, wherein the weight ratio of magnesium chloride (calculated as MgO) to the slurry containing the catalyst precursor was 1.2:100, and then filtered, 1.2 kg of water (the amount of water used for washing was 6 times the mass of the catalyst precursor) was added, washed at 25° C. for 0.2 h, and dried at 110° C. for 10 h to obtain a catalytic cracking catalyst C4;
[0141] Wherein, based on the total weight of the catalytic cracking catalyst, the Na in the catalytic cracking catalyst C4, calculated as Na2O, + The content is 0.18wt%, the phosphorus content calculated as P2O5 is 1.43wt%, and the magnesium content calculated as MgO is 0.85wt%.
[0142] Example 5
[0143] Prepared according to the method of Example 1, except that
[0144] In the process of preparing the rare earth modified molecular sieve, in step (a), 0.537 L (calculated as La2O3) of a LaCl3 solution with a concentration of 298 g / L is replaced with 0.67 L (calculated as La2O3) of a LaCl3 solution with a concentration of 298 g / L, so that the content of LaCl3 calculated as La2O3 in the NaY molecular sieve calculated on a dry basis is 20 wt %, and the other conditions are the same, to obtain a rare earth modified Y-type molecular sieve Z5;
[0145] In the process of preparing the catalytic cracking catalyst, the rare earth modified Y type molecular sieve Z1 is replaced by the rare earth modified Y type molecular sieve Z5, and the other conditions are the same, to obtain the catalytic cracking catalyst C5;
[0146] Wherein, based on the total weight of the catalytic cracking catalyst, the Na in the catalytic cracking catalyst C5, calculated as Na2O, is + The content is 0.13wt%, the phosphorus content calculated as P2O5 is 1.18wt%, and the magnesium content calculated as MgO is 0.94wt%.
[0147] Example 6
[0148] Prepared according to the method of Example 1, except that
[0149] In the process of preparing rare earth modified molecular sieve, in step (b), (32 g, 0.225 mol) ammonium oxalate monohydrate is replaced with (12.8 g, 0.09 mol) ammonium oxalate monohydrate, so that 1 wt% of La in the rare earth ion exchange slurry is 3+ The first precipitation was carried out (temperature was 80°C, time was 0.5h), and the other conditions were the same to obtain the rare earth modified Y-type molecular sieve Z6.
[0150] In the process of preparing the catalytic cracking catalyst, the rare earth modified Y type molecular sieve Z1 is replaced by the rare earth modified Y type molecular sieve Z6, and the other conditions are the same, to obtain the catalytic cracking catalyst C6;
[0151] Wherein, based on the total weight of the catalytic cracking catalyst, the Na2O in the catalytic cracking catalyst C6 is + The content is 0.18wt%, the phosphorus content calculated as P2O5 is 1.10wt%, and the magnesium content calculated as MgO is 0.92wt%.
[0152] Example 7
[0153] Prepared according to the method of Example 1, except that
[0154] In the process of preparing rare earth modified molecular sieve, in step (d), (25.6 g, 0.18 mol) of ammonium oxalate monohydrate is replaced with (6.4 g, 0.045 mol) of ammonium oxalate monohydrate, so that 0.5 wt% of La in the above cross-baked molecular sieve dry powder is 3+ A second precipitation was carried out (temperature was 25°C, time was 0.5 h), and other conditions were the same to obtain rare earth modified Y-type molecular sieve Z7;
[0155] In the process of preparing the catalytic cracking catalyst, the rare earth modified Y type molecular sieve Z1 is replaced by the rare earth modified Y type molecular sieve Z7, and the other conditions are the same, to obtain the catalytic cracking catalyst C7;
[0156] Wherein, based on the total weight of the catalytic cracking catalyst, the Na2O in the catalytic cracking catalyst C7 is + The content is 0.19wt%, the phosphorus content calculated as P2O5 is 1.17wt%, and the magnesium content calculated as MgO is 0.97wt%.
[0157] Comparative Example 1
[0158] (1) Preparation of rare earth modified molecular sieves
[0159] The preparation method is disclosed in CN200610087535.2, which specifically includes:
[0160] Take 1000g (dry basis weight) of NaY molecular sieve, slurry it with 8L of deionized water, add 0.385L (calculated as La2O3) of 312g / L RECl3 solution, add 240g of aluminum sulfate, exchange at 90°C for 1h, add 75g of ammonium bicarbonate, stir at constant temperature for 0.25h, filter, rinse with 5L of water, and then calcine the filter cake at 600°C and 100% water vapor atmosphere for 2 hours to obtain a cross-baked molecular sieve dry powder; take 1000g (dry basis weight) of this cross-baked molecular sieve dry powder, slurry it with 6L of deionized water, add 300g of ammonium sulfate, exchange at 75°C for 1h, filter, rinse with 6L of water, and dry the filter cake to obtain a rare earth modified Y-type molecular sieve DZ1;
[0161] (2) Preparation of catalytic cracking catalyst
[0162] Based on 100 parts of the dry mass of the catalyst, 30 parts by weight of the rare earth modified Y-type molecular sieve DZ1, 0.9 parts by weight of ammonium dihydrogen phosphate (calculated as P2O5) and water were mixed and slurried for 30 minutes, and then 52.1 parts by weight of kaolin, 7 parts by weight of aluminum sol, and 10 parts by weight of acidified pseudo-boehmite were added, and mixed at 25°C for 1 hour to obtain a slurry with a solid content of 37wt%, and then homogenized and spray-formed in sequence, and the obtained microspheres were calcined at 440°C for 30 minutes to obtain a catalytic cracking catalyst precursor;
[0163] Based on the dry basis of catalyst solid particles, 200 g of the catalytic cracking catalyst precursor was mixed with water to form a slurry containing the catalyst precursor with a solid content of 20 wt%, and then ammonium chloride was added and mixed, wherein the weight ratio of ammonium chloride to the slurry containing the catalyst precursor was 4:100, and then filtered, 0.8 kg of water (the amount of water used for washing was 4 times the mass of the catalyst precursor) was added, washed at 25° C. for 0.2 h, and dried at 105° C. for 10 h to obtain a catalytic cracking catalyst DC1;
[0164] Wherein, based on the total weight of the catalytic cracking catalyst, the Na2O in the catalytic cracking catalyst DC1 is + The content is 0.25wt%, and the phosphorus content calculated as P2O5 is 0.78wt%.
[0165] Comparative Example 2
[0166] (1) Preparation of rare earth modified molecular sieves
[0167] A rare earth modified Y type molecular sieve was prepared according to the method of Example 1, except that in step (b), no (32 g, 0.225 mol) ammonium oxalate monohydrate was added, and the other conditions were the same to obtain a rare earth modified Y type molecular sieve DZ2;
[0168] (2) Preparation of catalytic cracking catalyst
[0169] Based on 100 parts of the dry mass of the catalyst, 28 parts by weight of the rare earth modified Y-type molecular sieve DZ2, 1.5 parts by weight of ammonium dihydrogen phosphate (calculated as P2O5) and water were mixed and slurried for 30 minutes, and then 50.5 parts by weight of kaolin, 5 parts by weight of aluminum sol, and 15 parts by weight of acidified pseudo-boehmite were added, and mixed at 25°C for 1 hour to obtain a slurry with a solid content of 35wt%, and then homogenized and spray-formed in sequence, and the obtained microspheres were calcined at 470°C for 35 minutes to obtain a catalytic cracking catalyst precursor;
[0170] Based on the dry basis of catalyst solid particles, 200 g of the catalytic cracking catalyst precursor was mixed with water to form a slurry containing the catalyst precursor with a solid content of 20 wt%, and then ammonium chloride was added and mixed, wherein the weight ratio of ammonium chloride to the slurry containing the catalyst precursor was 3:100, and then filtered, 0.8 kg of water (the amount of water used for washing was 4 times the mass of the catalyst precursor) was added, washed at 25° C. for 0.2 h, and dried at 120° C. for 10 h to obtain a catalytic cracking catalyst DC2;
[0171] Wherein, based on the total weight of the catalytic cracking catalyst, the Na2O in the catalytic cracking catalyst DC2 is +The content is 0.22wt%, and the phosphorus content calculated as P2O5 is 1.42wt%.
[0172] Comparative Example 3
[0173] (1) Preparation of rare earth modified molecular sieves
[0174] A rare earth modified Y type molecular sieve was prepared according to the method of Example 2, except that in step (d), no (25.6 g, 0.18 mol) ammonium oxalate monohydrate was added, and the other conditions were the same to obtain a rare earth modified Y type molecular sieve DZ3;
[0175] (2) Preparation of catalytic cracking catalyst
[0176] Based on 100 parts of the dry mass of the catalyst, 32 parts by weight of the rare earth modified Y-type molecular sieve DZ3, 1.5 parts by weight of ammonium dihydrogen phosphate (calculated as P2O5) and water were mixed and slurried for 30 minutes, and then 45.5 parts by weight of kaolin, 8 parts by weight of aluminum sol, and 13 parts by weight of acidified pseudo-boehmite were added, and mixed at 25°C for 1 hour to obtain a slurry with a solid content of 35wt%, and then homogenized and spray-formed in sequence, and the obtained microspheres were calcined at 430°C for 35 minutes to obtain a catalytic cracking catalyst precursor;
[0177] Based on the dry basis of catalyst solid particles, 200 g of the catalytic cracking catalyst precursor was mixed with water to form a slurry containing the catalyst precursor with a solid content of 20 wt%, and then ammonium chloride was added and mixed, wherein the weight ratio of ammonium chloride to the slurry containing the catalyst precursor was 5:100, and then filtered, 1.2 kg of water (the amount of water used for washing was 6 times the mass of the catalyst precursor) was added, washed at 25° C. for 0.2 h, and dried at 100° C. for 10 h to obtain a catalytic cracking catalyst DC2;
[0178] Wherein, based on the total weight of the catalytic cracking catalyst, the Na2O in the catalytic cracking catalyst DC3 is + The content is 0.20wt%, and the phosphorus content calculated as P2O5 is 1.32wt%.
[0179] Comparative Example 4
[0180] (1) Preparation of rare earth modified molecular sieves
[0181] Prepared according to the method of Example 4, except that in step (b), no (25.6 g, 0.18 mol) of ammonium oxalate monohydrate and 5 mL of 28% industrial ammonia water were added, and in step (d), no (18 g, 0.187 mol) of ammonium carbonate was added, and the other conditions were the same, to obtain rare earth modified Y-type molecular sieve DZ4;
[0182] (2) Preparation of catalytic cracking catalyst
[0183] Prepared according to the method of Example 1, except that the rare earth modified Y type molecular sieve Z1 is replaced by rare earth modified Y type molecular sieve DZ4, and the other conditions are the same, to obtain catalytic cracking catalyst DC4;
[0184] Wherein, based on the total weight of the catalytic cracking catalyst, the Na2O in the catalytic cracking catalyst DC4 is + The content is 0.21wt%, the phosphorus content calculated as P2O5 is 1.09wt%, and the magnesium content calculated as MgO is 0.91wt%.
[0185] The physical properties of the rare earth modified molecular sieves (Z1-Z7 and DZ1-DZ4) prepared in Examples 1-7 of the present invention and Comparative Examples 1-4 are listed in Table 1.
[0186] Table 1
[0187]
[0188] Test Example 1
[0189] The rare earth modified molecular sieves (Z1-Z7 and DZ1-DZ4) prepared in Examples 1-7 and Comparative Examples 1-4 were subjected to a hydrothermal stability test. The test conditions included: 100 g (dry basis) of the rare earth modified molecular sieves (Z1-Z7 and DZ1-DZ4) were respectively tableted and then crushed into 20-40 mesh particles. After aging for 10 h at 800° C. in a fixed bed hydrothermal treatment device with 100% water vapor, the micro-activity index (MA) was measured on a catalytic cracking automatic micro-reaction activity assessor. The test results are listed in Table 2.
[0190] Table 2
[0191] Example Rare earth modified molecular sieve MA, wt% Example 1 Z1 72 Example 2 Z2 65 Example 3 Z3 73 Example 4 Z4 70 Example 5 Z5 71 Example 6 Z6 68 Example 7 Z7 66 Comparative Example 1 DZ1 60 Comparative Example 2 DZ2 61 Comparative Example 3 DZ3 58 Comparative Example 4 DZ4 61
[0192] Test Example 2
[0193] The catalytic cracking catalysts (C1-C7 and DC1-DC4) prepared in Examples 1-7 and Comparative Examples 1-4 were tested for reaction performance, and the test conditions included: adding the above catalytic cracking catalysts (C1-C7 and DC1-DC4) and the feedstock oil of the 3 million heavy oil catalytic unit of Lanzhou Petrochemical to the ACE heavy oil microreactor, and performing catalytic cracking (temperature of 510°C, weight ratio of the catalytic cracking catalyst to the feedstock oil of the 3 million heavy oil catalytic unit of Lanzhou Petrochemical was 5:1), and obtaining catalytic cracking products. Among them, the catalytic cracking products include: dry gas, liquefied gas, gasoline, diesel, heavy oil and coke, and the test results are listed in Table 3.
[0194] Table 3
[0195]
[0196] Note: 1- conversion rate of crude oil of 3 million tons heavy oil catalytic unit of Lanzhou Petrochemical; 2- refers to the sum of the yields of liquefied gas, gasoline and diesel.
[0197] The catalytic cracking catalyst provided by the present invention is characterized by good activity stability, high heavy oil conversion rate and high diesel yield by combining a rare earth modified molecular sieve with low sulfate radical, high crystallinity, strong acidity and good stability with a phosphorus source and a magnesium source. The catalyst is particularly suitable for heavy oil catalytic cracking. In the process of heavy oil catalytic cracking, it can not only show high catalytic cracking activity but also obtain a high diesel yield.
[0198] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalytic cracking catalyst, characterized in that: The catalytic cracking catalyst contains catalytic cracking active components, wherein the catalytic cracking active components contain: rare earth modified molecular sieve, phosphorus oxide and magnesium oxide; SO4 in the rare earth modified molecular sieve 2- Content ≤1wt%.
2. The catalyst according to claim 1, wherein The rare earth modified molecular sieve SO4 2- Content ≤ 0.5wt%, preferably 0.01-0.45wt%; and / or The rare earth modified molecular sieve has a crystallinity of 50-80%; and / or The sodium content in the rare earth modified molecular sieve is not more than 1.2 wt % calculated as Na2O, preferably 0.6-1.0 wt %; and / or The rare earth content in the rare earth modified molecular sieve is 5-20wt%, preferably 6-18wt% calculated as RE2O3; and / or Based on the total weight of the catalytic cracking catalyst, the phosphorus oxide is calculated as P2O5, and the magnesium oxide is calculated as MgO. The catalytic cracking catalyst contains: 15-30 weight percent of rare earth modified molecular sieve, 0.5-3 weight percent of phosphorus oxide, and 0.2-1.5 weight percent of magnesium oxide.
3. The catalyst according to claim 1 or 2, wherein The rare earth modified molecular sieve is a rare earth modified Y type molecular sieve; The catalytic cracking catalyst contains macroporous material, clay, the catalytic cracking active component and optionally a binder; Preferably, The macroporous material is selected from macroporous alumina and / or macroporous silica-alumina material, preferably macroporous silica-alumina material; and / or The clay is selected from at least one of kaolin, halloysite, porphyrite, diatomite and vesicle, preferably kaolin; and / or The binder is selected from at least one of silicon dioxide, aluminum oxide, and phosphorus pentoxide, preferably aluminum oxide.
4. The catalyst according to claim 1, wherein The catalytic cracking catalyst contains rare earth modified molecular sieve, macroporous material, binder, clay, phosphorus oxide and magnesium oxide. Based on the total weight of the catalytic cracking catalyst, the phosphorus oxide is calculated as P2O5 and the magnesium oxide is calculated as MgO. The catalytic cracking catalyst contains: 15-30 weight percent of rare earth modified molecular sieve, 2-15 weight percent of macroporous material, 5-30 weight percent of binder, 40-75 weight percent of clay, 0.5-3 weight percent of phosphorus oxide and 0.2-1.5 weight percent of magnesium oxide.
5. The catalyst according to claim 1, wherein The preparation method of the rare earth modified molecular sieve comprises the following steps: (1) exchanging rare earth ions on a Na-type molecular sieve to obtain a rare earth ion exchange slurry; (2) adding a first precipitant to cause a portion of the rare earth ions in the rare earth ion exchange slurry to undergo a first precipitation to obtain a first precipitation slurry; (3) the first precipitation slurry is filtered, subjected to a first ammonium sulfate exchange, subjected to a first water wash, and subjected to a first roasting in sequence to obtain a cross-exchanged and roasted molecular sieve dry powder; (4) adding a second precipitant to cause a second precipitation of some rare earth ions in the cross-calcined molecular sieve dry powder, and then sequentially performing a second ammonium sulfate exchange, a second water washing, and optionally a second calcination to obtain a rare earth modified molecular sieve.
6. The catalyst according to claim 5, wherein In step (1), The rare earth ion exchange process comprises: mixing the Na type molecular sieve with water and then adding a soluble rare earth source to perform the rare earth ion exchange; Preferably, The weight ratio of the Na-type molecular sieve to water is 1:(1.5-30), preferably 1:(2-5); and / or The mass ratio of the soluble rare earth source calculated as RE2O3 to the Na-type molecular sieve calculated as dry basis is 1-20:100, preferably 6-16:100; and / or The rare earth ion exchange conditions include: The temperature is 25-180°C, preferably 50-80°C; and / or pH 2.8-6.5, preferably 3.5-4.5; and / or The time is 0.3-3.5h, preferably 0.5-1.5h; More preferably, The silicon-aluminum ratio of the Na-type molecular sieve is 2-100:1, preferably 2-50:1; More preferably, the Na-type molecular sieve is at least one selected from NaY molecular sieve, NaHY molecular sieve, NaUSY molecular sieve, NaREHY molecular sieve and NaREUSY molecular sieve, preferably NaY molecular sieve and / or NaHY molecular sieve; and / or The soluble rare earth source is selected from chlorates and / or nitrates containing rare earth elements, wherein the rare earth is selected from at least one of lanthanum, cerium and yttrium, preferably lanthanum and / or yttrium.
7. The catalyst according to claim 5, wherein In step (2), The amount of the first precipitant is such that the molar ratio of the rare earth ions in the Na-type molecular sieve is 1-4wt% after the first precipitation, preferably such that the molar ratio of the rare earth ions in the Na-type molecular sieve is 1.5-2.5wt% after the first precipitation; Preferably, The conditions of the first precipitation include: The temperature is 25-180°C, preferably 50-80°C; and / or The time is 0.1-5h, preferably 0.1-2h; and / or The first precipitant is selected from at least one of ammonium carbonate, ammonium bicarbonate, ammonium oxalate, ammonium acetate, ammonia water and urea, preferably selected from at least one of ammonium carbonate, ammonium bicarbonate, ammonium oxalate and ammonia water.
8. The catalyst according to claim 5, wherein In step (3), The first ammonium sulfate exchange process includes: exchanging the filtered product with the first ammonium sulfate aqueous solution; Preferably, The weight ratio of the first aqueous ammonium sulfate solution to the Na-type molecular sieve is 5-50:100, preferably 10-25:100, calculated as ammonium sulfate; Preferably, the concentration of ammonium sulfate in the first aqueous ammonium sulfate solution is 20-400 g / L, preferably 120-250 g / L; and / or The conditions of the first ammonium sulfate exchange include: The temperature is 15-150°C, preferably 50-80°C; and / or The time is 0.1-5h, preferably 0.5-2h; and / or The amount of water used in the first water washing is 1-8 times, preferably 2-5 times, the weight of the Na-type molecular sieve; and / or The first calcination conditions include: 100% water vapor atmosphere; and / or The temperature is 400-700°C, preferably 500-650°C; and / or The time is 0.1-5h, preferably 0.5-3h.
9. The catalyst according to claim 5, wherein In step (4), The amount of the second precipitant is such that the content of the rare earth ions in the cross-roasted molecular sieve dry powder is 0.5-3wt% by molar ratio after the second precipitation, preferably such that the content of the rare earth ions in the cross-roasted molecular sieve dry powder is 1-2wt% by molar ratio after the second precipitation; Preferably, The conditions of the second precipitation include: The temperature is 15-40°C, preferably 20-30°C; and / or The time is 0.1-5h, preferably 0.1-2h; and / or The second precipitant is selected from at least one of ammonium carbonate, ammonium bicarbonate, ammonium oxalate, ammonium acetate, ammonia water and urea, preferably selected from at least one of ammonium carbonate, ammonium bicarbonate, ammonium oxalate and ammonia water; and / or The second ammonium sulfate exchange process comprises: exchanging the second precipitated product with a second aqueous ammonium sulfate solution; Preferably, The weight ratio of the second aqueous ammonium sulfate solution to the cross-baked molecular sieve dry powder is 5-50:100, preferably 10-25:100, calculated as ammonium sulfate; and / or Preferably, the concentration of ammonium sulfate in the second aqueous ammonium sulfate solution is 20-400 g / L, preferably 120-250 g / L; and / or The conditions of the second ammonium sulfate exchange include: The temperature is 20-85°C, preferably 50-80°C; and / or The time is 0.1-5h, preferably 0.1-2h; and / or The amount of water used in the second water washing is 1-8 times, preferably 2-5 times, the weight of the cross-baked molecular sieve dry powder; and / or The second calcination conditions include: 20-100% water vapor atmosphere; and / or The temperature is 400-700°C, preferably 450-650°C; and / or The time is 0.1-10h, preferably 0.5-5h; and / or Before the second precipitation, the cross-baked molecular sieve dry powder and water are mixed; Preferably, the weight ratio of the cross-baked molecular sieve dry powder to water is 1:(1.5-30), preferably 1:(2-5).
10. A method for preparing a catalytic cracking catalyst according to any one of claims 1 to 9, characterized in that: The preparation method comprises: The catalytic cracking active component is mixed and contacted with a macroporous material source and a clay source in a solution state to obtain a catalyst precursor, which is optionally shaped, and then optionally dried and calcined; Preferably, the preparation method comprises: (1) mixing the rare earth modified molecular sieve, phosphorus source and water to make a slurry, then adding a macroporous material source, a binder source and a clay source to mix and homogenize, dry and calcine to obtain catalyst solid particles; (2) The catalyst solid particles obtained in step (1), water, a magnesium source and optionally an ammonium source are mixed, filtered, washed with water and dried to obtain a catalytic cracking catalyst.
11. The preparation method according to claim 10, wherein: In step (1), Based on 100 parts of the dry basis weight of the catalyst and the phosphorus source in terms of P2O5, 15-30 parts of a rare earth modified molecular sieve, 0.5-3 parts of a phosphorus source, 2-15 parts of a macroporous material source, 5-30 parts of a binder source, 40-75 parts of a clay source and water are mixed to prepare a slurry with a solid content of 25-50wt%; Preferably, based on 100 parts of the dry basis mass of the catalyst, the phosphorus source is calculated as P2O5, 18-27 parts of the rare earth modified molecular sieve, 0.9-2 parts of the phosphorus source, 3-7 parts of the macroporous material source, 5.5-25 parts of the binder source, 45-65 parts of the clay source and water are mixed to prepare a slurry with a solid content of 35-45wt%; More preferably, The phosphorus source is selected from at least one of diammonium hydrogen phosphate, ammonium dihydrogen phosphate and ammonium phosphate, preferably diammonium hydrogen phosphate; and / or The macroporous material source is selected from macroporous alumina and / or macroporous silica-alumina material, preferably macroporous silica-alumina material; and / or The binder source is selected from at least one of aluminum sol, acidified pseudo-boehmite, acidic silica sol and phosphate aluminum sol, preferably aluminum sol and / or acidified pseudo-boehmite, more preferably aluminum sol and acidified pseudo-boehmite; and / or The clay source is selected from at least one of kaolin, halloysite, porphyrite, diatomite, and vesicle, preferably kaolin; and / or The conditions for the calcination include: The temperature is 400-500°C, preferably 450-480°C; and / or The time is 20-50 min, preferably 25-40 min.
12. The preparation method according to claim 10 or 11, wherein: In step (2), Calculated on a dry basis of catalyst solid particles, magnesium source is calculated as MgO, The weight ratio of water to catalyst solid particles is 0.5-35:1; and / or The amount of the magnesium source added is 0.2-1.5wt%, preferably 0.6-1.2wt%; Preferably, The magnesium source is selected from magnesium chloride and / or magnesium nitrate, preferably magnesium chloride; and / or The ammonium source is selected from ammonium chloride and / or ammonium nitrate, preferably ammonium chloride; and / or The conditions of the water washing include: The temperature is 20-100°C, preferably 25-50°C; and / or The time is 0.1-0.3h, preferably 0.15-0.25h.
13. Use of the catalytic cracking catalyst according to any one of claims 1 to 9 in catalytic cracking of heavy oil.
Citation Information
Patent Citations
Catalytic cracking catalyst and preparation method thereof
CN109304212A
Catalytic cracking catalyst and preparation method thereof
CN114433253A